La contaminación del Río Jubones y su incidencia en las enfermedades de la piel en los pobladores del sitio Galayacu cantón-Pasaje - Ortega Machuca, Kennia V. (2006)
The resource more important hydric for our country is the river Jubones, since of him she/he takes the water for the watering of the banana tree plantations and of short cycle, and equally its waters are used in the industry and it stops human consumption.